Work‐related behaviour and experience patterns of nurses in different professional stages and settings compared to physicians in Germany. (20th June 2012) - Voltmer, Edgar; Wingenfeld, Katja; Spahn, Claudia; Driessen, Martin; Schulz, Michael
ABSTRACT Working in a health‐care profession is correlated with high levels of stress and potential burnout that are likely to increase over time. Few studies differentiate psychosocial stress between nurses in different clinical settings or professional stages. In this cross‐sectional study, we compared the work‐related behaviour and experience of nurses (n = 389) and physicians (n = 344) and of nurses across different career stages and clinical settings in Germany. Nurses had the lowest proportion of a healthy behaviour and experience pattern (11.6%) compared with student nurses (32.6%), senior nurses (25%), and physicians (16.7%). They also had the highest proportion of a burnout‐related behaviour and experience pattern (32.8% vs 26.1% of student nurses, 18.3% of senior nurses, and 27.3% of physicians). In comparison with medical nurses, psychiatric nurses presented a significantly (P < 0.01) lower proportion with a healthy (10.6% vs 21.8%) and burnout‐related behaviour pattern (23.5% vs 29.6%), and a higher proportion showing a low commitment to work (61.4% vs 34.4%). Differences in health‐related dimensions were primarily observed in the domains of professional commitment and stress resistance. The observed differences in behaviour and experience patterns as a function of health‐care settings and career stages emphasize the need for specific interventions.